Commodification of the TikTok Account @meetnitelivemetrotv In Increasing Audience Interest in Consuming News - Bayquni, Bayquni; Prakoso, Jatayu Hadi (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study aims to analyze the commodification strategies employed by the TikTok account @meetnitelivemetrotv in an effort to increase audience interest in consuming news in the digital age. As a conventional news institution, Metro TV is undergoing a radical transformation to maintain relevance through new media platforms. This study uses qualitative methods with a political economy of media approach and Mark Poster's New Media theory to examine this commodification phenomenon. The research results show that commodification occurs in three main dimensions. First,commodification of content. This is done by recontextualizing news into snackable entertainment products (newstainment) using a stand-up comedy style to reduce the audience's cognitive barriers. Second, commodification of the audience This occurs through the capitalization of precise attribution data, where the identities and behaviors of the younger generation (Gen Z) are configured as valuable commodities for advertisers. Third, commodification of workers involves mobilizing audience digital interactions (such as likes, shares, and comments) that are considered voluntary “digital work” to increase account valuation in the face of algorithms. The conclusion of this study confirms that Metro TV successfully transformed the use value of news into digital exchange value through narrative deconstruction and database utilization. Crucial to the success of this strategy lies in narrative efficiency, a more humanized brand personification, and the ability to present realistic audience behavior data. This research confirms Mark Poster's theory that in the new media ecosystem, there is a shift from traditional mass communication to interactive communication mediated by databases and algorithms.